Implementation of General Elections in National History - Cici Fitri Bety; T Heru Nurgiansah (CV. Rayyan Dwi Bharata, 2024)
General elections are a mechanism for determining the people's representatives who will occupy the people's representative institutions and elect the president and vice president. The history of General Elections in Indonesia has unique characteristics that are interesting to research, with several elections that have been held since the Old Order era in 1955, the New Order in 1971, 1977, 1982, 1987, 1992, and 1997, as well as during the ongoing Reformation period. from 1999 to 2019. This research was conducted through literature study with a focus on how general elections were carried out from the beginning of independence until 2019. The results of the research show that elections during the Old Order era could be considered democratic, characterized by the participation of many political parties. However, during the New Order era, this democracy declined along with the dominance of the Soeharto regime. Meanwhile, general elections during the Reformation period, especially in 2004, became more democratic. The 2019 elections were held simultaneously for the first time, although many obstacles occurred in its implementation. The author hopes that this journal will be useful in increasing academic insight regarding the implementation of general elections, as well as providing political learning for the community and input for subsequent elections.